SHOULD A FLOATING CHARGE BE INTRODUCED IN THE JUDICIARY OF THE REPUBLIC OF SERBIA? - Čubrilović Stamenić, Bosiljka (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
The article analyses the floating charge in Anglo-Saxon law systems and its equivalents in the European-continental legal order. In addition, the author examines the elementary determinants recognized as common to the institute of a floating charge and its equivalents in comparative: constitution, object, subjects, legal effect inter partes, the legal effect of registration, priority order, and settlement, underlining their particularities, underlining their particularities. Finally, the author provides a brief overview of the current regulation of the movable property guarantee system in the Republic of Serbia, and the question of justifying a possible standardization of the institute of the floating charge in Serbian legislation is examined. The author concludes that the current legal framework of the pledge of movable property in the law of the Republic of Serbia not only satisfies the economic interests of the business community but is also in line with the spirit of its (pledge)legal tradition.